Seismic Characteristics of Mount Agung during the October–November 2017 Period - W.T. Baskoro; I.K. Putra; N.N. Wendri; I.N. Artawan; V.C.W. Putri; S. Sismanto (Jurnal Penelitian Pendidikan IPA, 2026)
Mount Agung, a prominent stratovolcano in Bali, Indonesia, exhibited a significant increase in volcanic activity between October and November 2017 after 54 years of dormancy. This study investigates the seismic characteristics of this unrest period using waveform and spectral analysis of data from three monitoring stations: Abang (ABNG), Cegi (CEGI), and Yeh Kori (YHKR). The results indicate that seismicity was dominated by intermediate-to-deep volcanic earthquakes (VA and VB types), reaching a peak on October 18, 2017, with 679 VA and 266 VB events recorded. Spectral analysis through Fast Fourier Transform (FFT) revealed dominant frequencies ranging from 3.8 to 10.1 Hz, representing brittle failure mechanisms within the rigid volcanic edifice. A critical transition was observed in late November, where discrete high-frequency events declined and were replaced by continuous volcanic tremors, signaling a shift from a closed to an open magmatic system. This "seismic lull" accompanied by tremor signals, indicates the establishment of a stable conduit, facilitating magma migration toward the surface. These findings underscore the importance of spectral characteristics and event-type transitions as vital precursors for eruptive forecasting and volcanic hazard mitigation.